Characterization and Application of Greener-Activated Coal Fly Ash for Phosphate Adsorption in Donan River Water Samples - Rohmah, Dini Novi; Nur Mas'udah, Aldina Khoerunnisa; Sudariasri, Vida Zenitha; Boikh, Mesakh Trywira Wibowo; Moneteringtyas, Prisca Caesa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The Karangkandri PLTU (Steam Power Plant) Industry in Cilacap is one of the large industries in the Cilacap industrial area, which has abundant coal-burning waste in the form of fly ash. The excess fly ash from PLTU Karangkandri can be used for the adsorption of polluted phosphate ions in the Donan River. The aim of this research is to determine the characterization of fly ash as an adsorbent using FTIR (Fourier Transform Infra-Red), XRD (X-Ray Diffraction), and XRF (X-Ray Fluorescence) instruments and its ability to adsorb phosphate ions in a polluted water sample. The first stage of this research was to take water samples from the Donan River at the 3 most polluted points. The second stage was to activate fly ash using wet grinding and hydrothermal methods as well as characterization of fly ash using FTIR, XRD, and XRF instruments. Then the effectiveness of the fly ash adsorbent in adsorbing phosphate ion was tested by using the spectrometric method. The analysis was carried out with the influence of mass variations in the adsorbent of 50, 100, 150, and 200 grams per 500 ml of water sample. This research found that activated fly ash by greener activation can removed 82,8% phosphate ion with 0,5g fly ash, remove 72.4% phosphate ion with 1 gram fly ash, removed 77.6% phosphate ion with 2 grams of fly ash. And the best one is 5 grams of fly ash can remove 93.2% phosphate ion.